Città sospese fra capi e fiumare Strategie identitarie - Arena, Marinella (Forme del disegno, 2023)
Every representation of the world, every drawing, every critical reflection ultimately describes ourselves; it defines us as people and as researchers. The text Cities suspended between capes and rivers collects the results of a research carried out for over a decade, from 2011 to 2023, which involved six small towns on the Sicilian Ionian coast: Forza d'Agrò, Casalvecchio, Mandanici, Fiumedinisi, Alì and Itala. The synthetic restitution of tangible and intangible data is graphically described in six reports dedicated to each city. The intent is to build an "identity map" characterized by the overlapping of numerous levels of interpretation: some analytical and structured, others abstract and synthetic, still others nuanced and playful.